Aggressive effects of prioritizing popularity in early adolescence. Issue 3 (11th December 2013) - Cillessen, Antonius H.N.; Mayeux, Lara; Ha, Thao; de Bruyn, Eddy H.; LaFontana, Kathryn M.
<x xml:space="preserve">Abstract</x> This study examined the moderating effects of prioritizing popularity on the association between early adolescents' popularity and their aggressive, leadership, and prosocial behaviors with peers. Participants were 288 14‐year‐olds from The Netherlands who completed a sociometric instrument and an assessment of how much they prioritized popularity over other personal goals. Results indicated that prioritizing popularity was distinct from actual popularity in the peer group. Further, prioritizing popularity moderated the association of popularity with aggressive and leadership behaviors, with adolescents who were both popular and who prioritized popularity being particularly aggressive and scoring high on leadership behaviors. This trend was especially true for boys. The same moderating effect was not found for prosocial behaviors. Motivational and social‐cognitive factors in the dynamics of peer popularity are highlighted. Aggr. Behav. 40:204–213, 2014. © 2013 Wiley Periodicals, Inc.